Measuring Human Centred Design (HCD) practices in software development in industry / Sarful Azman Abdullah - Abdullah, Sarful Azman (2017)
The demand to develop a high-quality system that covers effectiveness, efficiency and satisfaction to the end users is growing tremendously and the focus on the system usability has increasing significantly due to being considered as a main factor to produce a good and usable system. Usability has become a critical quality factor and it requires the adoption of a human-centered approach in the software development process. There are organizations that have been adopted the HCD however, the level of adoption is still unknown. As such, this research is conducted as to investigate and measure the implementation of HCD practices in the current software development in industry. In order to determine the level of Human Centred Design (HCD) adoption in software development companies, Human Centred Design Adoption Model (HCDAM) has been used. A qualitative approach is used in this study whereby an interview questions has been constructed based on HCDAM key activities, to identify the perception made by the IT professional. The result points that little evidence is available on the adoption of HCD during the initiation and design process where almost all of the participants have initiate an HCD practice such user involvement. With only thirteen (13) participants, it is quite difficult to generalize the outcome. Bigger group of participants with various experiences and background would be considered valuable for this kind of study. Future study needs to explore the most fundamental foundations from where IT practitioner's goal and assumptions. This understanding can facilitate them to apply HCD in the entire software development process hence, create a positive experience and eventually resulted in high quality and usable product.